2021
DOI: 10.3390/land10060564
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Characteristics and Driving Factors of Wetland Landscape Pattern Change in Henan Province from 1980 to 2015

Abstract: The study of the temporal and spatial evolution of wetland landscapes and its driving factors is an important reference for wetland ecological restoration and protection. This article utilized seven periods of land use data in Henan Province from 1980 to 2015 to extract the spatial distribution characteristics of wetlands and analyze the temporal and spatial changes of wetlands in Henan Province. Transfer matrix, landscape metrics, correlation analysis, and redundancy analysis were applied to calculate and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The analysis found that under different buffer scales, urban, rural residential, farmland, gardenland, grassland and other land types all were positively correlated with the number of floating debris spots. The analysis results were similar to those of Xia Huijuan et al (Li et al, 2021;Wang et al, 2021;Xia et al, 2021) Rural settlements, farmland, and the number of floating debris spots had strong positive correlations. Weak positive correlations were found with urban, gardenland, and grasslands.…”
Section: Effects Of Land Use Types On Floating Object At Different Sp...supporting
confidence: 84%
“…The analysis found that under different buffer scales, urban, rural residential, farmland, gardenland, grassland and other land types all were positively correlated with the number of floating debris spots. The analysis results were similar to those of Xia Huijuan et al (Li et al, 2021;Wang et al, 2021;Xia et al, 2021) Rural settlements, farmland, and the number of floating debris spots had strong positive correlations. Weak positive correlations were found with urban, gardenland, and grasslands.…”
Section: Effects Of Land Use Types On Floating Object At Different Sp...supporting
confidence: 84%
“…Regarding ecological surroundings factors, compared with the situation before 2010, when terrain factors and soil factors were dominant, the influence of climate factors on wetland reduction increased after 2010. Climate changes such as reduced rainfall, increased temperatures, or extreme weather, intensify the reduction of wetlands to some extent (Li et al 2021;Li et al 2020b). In urban gradienttype regions, anthropogenic interference is most severe.…”
Section: Fig 19 Interaction Results Of Driving Factors In Agricultura...mentioning
confidence: 99%
“…(2) Land use demands and land use transfer matrix rules (2) Land use demands and land use transfer matrix rules For the model calibration and prediction, the historical (2000-2020) and future land use demands (2035) were prepared. We used the method for linear regression [52], which can project future land use demands for a specific period while outputting the historical land use amounts. Table 3 shows the land use demands.…”
Section: Research Frameworkmentioning
confidence: 99%